2016
DOI: 10.2519/jospt.2016.5979
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Stabilization Exercises Plus Manual Therapy to Those of Stabilization Exercises Alone in Patients With Nonspecific Mechanical Neck Pain: A Randomized Clinical Trial

Abstract: Therapy, level 1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 65 publications
6
48
2
1
Order By: Relevance
“…Findings of this study also correlated with those of Celenay et al (2016) who showed that stabilization exercises combined with manual therapy were superior to stabilization exercises alone for improving pain, disability, range of motion and quality of life in mechanical neck pain [27].…”
Section: Discussionsupporting
confidence: 65%
“…Findings of this study also correlated with those of Celenay et al (2016) who showed that stabilization exercises combined with manual therapy were superior to stabilization exercises alone for improving pain, disability, range of motion and quality of life in mechanical neck pain [27].…”
Section: Discussionsupporting
confidence: 65%
“…MNP causing severe discomfort affect patient's daily life and ability to work [5,6]. It is characterized by structures and functional features within the cervical spine when it persisted, it is developed into chronic MNP [7][8][9]. The exact cause of chronic MNP is not completely clear [5].…”
Section: Introductionmentioning
confidence: 99%
“…Poor thoracic spine mobility was treated in neck pain by thoracic spine manipulation or mobilization with acute positive effects on neck pain and motions (14,15). Otherwise, mobility and stability exercises or additional therapies related to the thoracic region may be useful treatments for pain, range of motion, disability, and quality of life in patients with CNP (16,17). Although sagittal thoracic spinal curvature and mobility insufficiency in neck pain are a matter of interest, contradictory results have been mentioned in the literature (6,10,13,18,19).…”
Section: Introductionmentioning
confidence: 99%